EXTRADITION IN CRIMINAL JUSTICE SYSTEM RELATED TO FOREIGN JURISDICTION - Maringka, Jan Samuel (Pattimura Law Journal, 2017)
On extradition law in Indonesia is based from the fact that since the adoption of the Act in 1979, there have been fundamental changes in the criminal procedure ode in Indonesia, namely the enactment of Law No. 8 of 1981 on Criminal Proceedings and has the ratification of the International Covenant on Civil and Politics Rights (International Convention on Civil and political Rights, abbreviated as ICCPR) under Law No. 12 of 2005 which requires Indonesia to immediately adjust its positive legal provisions in accordance with the principles set out in the ICCPR. Considering the purpose of extradition implementation as an effort to support law enforcement process and related to examination process in extradition case which is not different from the stages of case handling process as regulated in criminal procedure law, it is necessary to affirm the concept of extradition as an integral part of the enforcement process law so that the principle of due process can be implemented consequently in the process of extradition implementation.